Online information and support for carers of people with young‐onset dementia: A multi‐site randomised controlled pilot study. (26th July 2019) - Metcalfe, Anna; Jones, Bridget; Mayer, Johannes; Gage, Heather; Oyebode, Jan; Boucault, Sarah; Aloui, Sabrina; Schwertel, Uta; Böhm, Markus; Tezenas du Montcel, Sophie; Lebbah, Said; De Mendonça, Alexandre; et al.
Abstract : Objectives: The European RHAPSODY project sought to develop and test an online information and support programme for caregivers of individuals diagnosed with young onset dementia. The objectives were to assess user acceptability and satisfaction with the programme and to test outcome measures for a larger effectiveness study. Design: A pilot randomised controlled trial in England, France, and Germany was conducted with 61 caregivers for adults with young onset Alzheimer's disease or frontotemporal degeneration. Evaluations at baseline, week 6, and week 12 assessed user acceptability and satisfaction. Use of the programme was measured from online back‐end data. Qualitative feedback on user experiences was collected via semi‐structured interviews. Measures of caregiver well‐being (self‐efficacy, stress, burden, frequency of patient symptoms, and caregiver reactions) were explored for use in a subsequent trial. Results: Participants logged in online on average once a week over a 6‐week period, consulting approximately 31% of programme content. Seventy percent of participants described the programme as useful and easy to use. Eighty‐five percent expressed intent to use the resource in the future. Reductions in reported levels of stress and caregivers' negative reactions to memory symptoms were observed following use of the programme. Conclusions: Results indicated that the RHAPSODY programme was acceptable and useful to caregivers. The programme may be complementary to existing services in responding to the specific needs of families affected by young onset dementia. Distribution of the programme is underway in England, France, Germany, and Portugal.